PENGARUH PERBANDINGAN TEPUNG TAPIOKA DAN TEPUNG JAMUR TIRAM PUTIH (Pleurotus Oestreatus) TERHADAP VOLUME PENGEMBANGAN, KADAR PROTEIN DAN ORGANOLEPTIK KERUPUK [Effect of tapioca and white oyster mushroom (Pleurotus oestreatus) flour comparison on expansion volume, protein content and sensoric characteristics of crakers] - Fibra Nurainy; Ribut Sugiharto; Dewi Wulan Sari (Jurnal Teknologi & Industri Hasil Pertanian, 2015)
Oyster mushroom flour (Pleurotus oestreatus) is an alternative form of half end product from oyster mushroom, due  its durability in storage  and can be applied in varous processed food  such as cracker. This flour can be used for food crakers which contains high protein and fiber content since it contains. 17,50% of protein and 14,12% of fiber. This condition is suitable for producing crackers. The research was conducted to find out the best comparison of tapioca and oyster mushroom flour to produce the best characteristics of oyster mushroom flour crackers. The characteristics include expansion volume, sensory, and protein content. This research was designed in a Completely Randomized Block Design with 4 replication. The treatments had 6 levels comparison of tapioca and oyster mushroom flour: L1 (0%: 100%), L2 (5%: 95%), L3 (10%: 90%), L4 (15%: 85% ), L5 (20%: 80%); L6 (25%: 75%). respectively data were analiyzed with Anova to find out the treatment effects, then the data were further analyzed with Honestly Significant Difference (HSD) test on level of 5% to find the best comparison. The best comparison was L5 (20% oyster mushroom flour and 80% tapioca) which resulted crackers, with expansion volume of 272.063%, and protein content 7.636% respectively. The crackers also had a crunchy texture and rather-typical of oyster mushroom flour aroma.Keywords: crakers, oyster mushroom flour, sensory